2020
DOI: 10.9789/2175-5361.rpcfo.v12.7178
|View full text |Cite
|
Sign up to set email alerts
|

Experience of women in labor with the use of flowers essences

Abstract: OBJETIVO: O estudo descreve a vivencia de mulheres submetidas ao uso de essências florais como terapia não farmacológica para o alivio da dor e ansiedade durante o trabalho de parto. MÉTODOS: Pesquisa descritiva exploratória, de conteúdo qualitativo, realizada com 30 parturientes, em um centro de parto normal público, intra-hospitalar da cidade de São Paulo. RESULTADOS: Constatou-se que os efeitos da terapia floral, atuaram em sinergia, na redução dos sintomas de estresse-medo-tensão, além do aumento d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
13

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 17 publications
0
20
0
13
Order By: Relevance
“…A qualitative study, with the aim of describing the experience of women undergoing the use of flower essences as a non-pharmacological therapy for pain and anxiety relief during labor, carried out in a Normal Childbirth Center, it was observed that the use of flower essence provided, according to report of nurses who assisted them, calm, relaxation, concentration and courage to women, facilitating the process of birth (18) .…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study, with the aim of describing the experience of women undergoing the use of flower essences as a non-pharmacological therapy for pain and anxiety relief during labor, carried out in a Normal Childbirth Center, it was observed that the use of flower essence provided, according to report of nurses who assisted them, calm, relaxation, concentration and courage to women, facilitating the process of birth (18) .…”
Section: Discussionmentioning
confidence: 99%
“…Tendo como foco na primeira fase do parto, o uso de óleos calmantes e sedativos tais como lavanda e camomila são recomendados, assim com outros tipos de óleos como olíbano que possuem ações relaxantes, auxiliam na respiração e devem ser utilizados na fase de transição do primeiro período do parto. Atentando-se para a segunda fase, os aromas mais fortes e apimentados podem promover uma sensação de força e antecipação do trabalho de parto, como o jasmim, pois aumenta as contrações uterinas (LARA et al, 2020).…”
Section: Resultados E Discussõesunclassified
“…The experience of vaginal delivery, when anchored by respect and safety, can enable women a differentiated existential experience, generating a sense of competence as a mother and person. In addition, it can provoke positive affective memories related to motherhood and physical and emotional well-being for being free from the painful sensation caused by the surgical wound (5) .…”
Section: Discussionmentioning
confidence: 99%
“…The literature points out that the choice of cesarean section involves a number of factors, including family issues, fear of pain, fear of complications for the baby and media influence when relating vaginal delivery to suffering and, above all, the indication of the obstetrician. Another aspect inherent to the choice of cesarean section is related to the scarcity of dialogue between pregnant women and health professionals during pregnancy about the real indications of cesarean section, a fact that contributes to the fear of delivery and the desire for the surgical route (4)(5) .…”
Section: Introductionmentioning
confidence: 99%